PENERAPAN MODEL PEMBELAJARAN PBL (PROBLEM BASED LEARNING) UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF KIMIA PESERTA DIDIK PADA MATERI STRUKTUR ATOM KELAS X 3 SMA OIKOUMENE MANOKWARI - Ceyza Dinda Hapsari; Ramlah Ramlah (Arfak Chem: Chemistry Education Journal, 2021)
AbstractThis study aims to improve student learning outcomes in class X 3 SMA OIKOUMENE Manokwari by using the PBL learning model on the atomic structure material. This study used a collaborative classroom action research method with a chemistry teacher for two cycles, each cycle consisting of two meetings. One meeting includes the stages of planning, implementation, observation and reflection. The results showed that the PBL (Problem Based Learning) model could improve the cognitive learning outcomes of X 3 grade students at SMA OIKOUMNE Manokwari. This is indicated by the final data acquisition that in the first and second cycles the first and second meetings each obtained an average score of 41.6666 and 60.4166 which increased in the second cycle at the third and fourth meetings to 76.25 and 83.3333 with student completeness reach100%. Keywords: Problem Based Learning, Learning Results, Atomic Structure, Class Action Research, Oikoumene High School